Self-Control as A Mediator of Local Wisdom-Based Character Education on Instant Gratification - Haribowo, Sigit Surya; Ai Elis Yuliati; Diar Widyardi; Parlis Lawalata; Ruslan Abdul Gani (International Journal of Business and Quality Research, 2025)
This study explores the rising trend of instant gratification among children and emphasizes the importance of strengthening character education grounded in local wisdom values to enhance self-control. Using a quantitative survey approach, data were collected through the distribution of questionnaires and subsequently analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach via the SmartPLS software 4. The research findings indicated that the internalization of character education grounded in local wisdom had a positive and significant effect on children’s self-control, while self-control negatively impacts instant gratification behavior. However, no direct significant relationship was found between character education and instant gratification. Mediation analysis confirms that self-control significantly mediates this relationship. These findings suggest that enhancing local wisdom–based character education can improve children’s self-control and reduce the tendency toward instant gratification, promoting more adaptive, long-term–oriented behaviors.